Communication Convergence in Village Development Program (Case: Village Fund in Sungai Kali Village, South Kalimantan) - Oki Gusri Anto (Jurnal Komunikasi Pembangunan, 2021)
Development and communication are two inseparable factors because a successful development cannot come up without the communication role as a strategy to realize a community welfare. The social inequality and poverty of today is caused by the development that is not in line with the community’s real needs or expectations. This triggers disagreements or non-convergent communication among all resource managers in the village. This study uses the theoretical approach of convergence communication model to examine factors that influence the development gaps in terms of individual characteristics, and the supporting environment available and to formulate convergent strategies to solve development gaps. This research is designed with a quantitative approach and qualitative data to identify social behaviors and symptoms in the community. The results showed that communication convergence does not occur in the development programs, which could be affected by low education, income levels and inappropriate policies applied in development to achieve common development goals.